2009
DOI: 10.1002/prca.200780098
|View full text |Cite
|
Sign up to set email alerts
|

Protein carbonylation in kidney medulla of the spontaneously hypertensive rat

Abstract: Enhanced generation of ROS has been reported in models of hypertension such as the spontaneously hypertensive rat (SHR). Impairment of kidney function has been implicated in development and progression of hypertension, and the renal medulla appears to play an important role in regulating long-term blood pressure. A key biomarker of oxidative stress is the formation of protein carbonyls, which we set out to characterize in the SHR medulla. We identified 11 proteins that were differentially carbonylated in SHR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…The medulla is an area that is significant in determining the level at which blood pressure may be set (7) and is a relatively hypoxic area and under oxidative stress (1). This is exacerbated in hypertension as demonstrated in recent proteomic studies in the medulla of the spontaneously hypertensive rat where there was enhanced nitration of proteins involved in NO signaling and antioxidant defense (22) as well as raised carbonylation of enolase 1 and catalase (23). Lenda and Boegehold (14) reported that exposure of rats to a high-salt diet resulted in a raised oxidant activity within the walls of arterioles in the skeletal microvasculature which they attributed to increased NAD(P)H oxidase activity (15).…”
mentioning
confidence: 92%
“…The medulla is an area that is significant in determining the level at which blood pressure may be set (7) and is a relatively hypoxic area and under oxidative stress (1). This is exacerbated in hypertension as demonstrated in recent proteomic studies in the medulla of the spontaneously hypertensive rat where there was enhanced nitration of proteins involved in NO signaling and antioxidant defense (22) as well as raised carbonylation of enolase 1 and catalase (23). Lenda and Boegehold (14) reported that exposure of rats to a high-salt diet resulted in a raised oxidant activity within the walls of arterioles in the skeletal microvasculature which they attributed to increased NAD(P)H oxidase activity (15).…”
mentioning
confidence: 92%
“…These investigators suggested that the sulfenated and carbonylated proteins could be targets of enhanced ROS generation with ROS acting as a signaling molecule and not as the direct inducer of oxidative damage. Some of the proteins identified by Tyther et al (76,77) are known to be redox sensitive and importantly involved in metabolism, antioxidant defense, and regulation of nitric oxidase synthase. However, only six out of 53 of the sulfenated proteins and four out of 12 of the carbonylated proteins were mitochondrial, none of which were differently expressed in the present mTAL study.…”
Section: Proteomic Analysis Of Mtal Mitochondria In Hypertensionmentioning
confidence: 99%
“…A proteomic analysis of whole medullary tissue by Tyther et al showed that protein sulfenation (76) and protein carbonylation (77) were enhanced in the renal medulla of SHR rats compared with normotensive Wistar rats. These investigators suggested that the sulfenated and carbonylated proteins could be targets of enhanced ROS generation with ROS acting as a signaling molecule and not as the direct inducer of oxidative damage.…”
Section: Proteomic Analysis Of Mtal Mitochondria In Hypertensionmentioning
confidence: 99%
“…In a large cohort of Chinese adults, plasma reactive carbonyl species was positively associated with blood pressure levels and was found to be an important risk factor for developing hypertension (36). Nitration of proteins, especially modification of tyrosine to 3-nitrotyrosine, is another form of redox modification and is increased in serum proteins in patients with hypertension, chronic kidney disease, and diabetes (25,131,217).…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%